(untitled) (Gestão & Regionalidade, 2016)
The Brazilian credit market has long suffered from macroeconomic instability and high inflation. However, since inflation was controlled and the implementation of the Real Plan in 1994, the amount of credit extended to households increased substantially. The objective of this study is to evaluate the evolution of credit in Brazil in recent times, showing how the policies adopted by the government influenced household consumption. In recent years, economic growth has been underpinned in consumption, mainly by the economic and social policies adopted. This allowed greater access to goods and services, but lower interest in investment and savings accounts, which directly impacts the development and performance of economic activity. These surveys are analyzed with others contained in the article, corroborating the argument of credit expansion and the main contributions and needs for future studies and monitoring, based on the work line which studies institutional variables.